A Model of Preparing Future Teachers for Professional Activity Based on Coaching Technologies (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article addresses the important task of developing a modern education system capable of responding to rapidly changing societal demands, fostering creativity, critical thinking, and self-improvement. In achieving this goal, the role of the teacher is radically changing: from the traditional transmitter of knowledge to a guide-facilitator, that is, a coach helping to unlock the student's personal and intellectual potential. Therefore, integrating coaching technologies into the training of future teachers and developing effective models for their preparation for professional work are relevant. This article presents the results of a study on the professional development of future teachers based on coaching technologies.